Impact of community based training on medical undergraduates skills upgradation regarding infant and young child feeding practices: A mixed method study - Tovia Stephen; Kalaiselvi Selvaraj; Joy Bazroy; Vincent Antony; Zile Singh; Anil J Purty (Wolters Kluwer Medknow Publications, 2018)
Background: Despite various reforms brought in health care service delivery there is always a gap between community and health care providers. Hence there is a need to explore the successful strategies to reorient the medical students towards public health relevant community needs. Objective: This study aimed to assess the feasibility and impact of community based field training imparted among medical undergraduates to identify problems related to infant and young child feeding practices and design appropriate interventions. Material and Methods: This study is a mixed method study where improvement of knowledge were assessed quantitatively through quasi experimental pre-post study design. Difference in cumulative score obtained after training was compared using student's t test. Perception of students and mentor's views on this approach in terms of benefits and challenges were explored during in-depth interviews. Transcripts of qualitative interviews were analysed using manual content analysis. Results: Total of 781 infant and young children from 30 villages were surveyed by 36 medical undergraduates. There was significant improvement in knowledge on feeding practices from the baseline [baseline mean (SD) score: 3.3 (1.5); post training mean (SD) score: 6.5 (1.1), p<0.001]. Mentors of the opinion that this community based approach had facilitated the students to acquire skills on management, communication, team spirit and professional attitude. Students had opportunity to assess spectrum of illness and the co-existing social conditions in their natural setting. Conclusion: Students as well as other stakeholders were more positive and overwhelmingly supporting this approach. This approach is feasible with better planning, institute cooperation and commitment.